2002
DOI: 10.4049/jimmunol.169.5.2587
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB Activity by a Membrane-Transducing Mutant of IκBα

Abstract: The transcription factor NF-κB is regulated by the IκB family of proteins. The nonphosphorylatable, nondegradable superrepressor IκBα (srIκBα) mutant is a potent inhibitor of NF-κB activity when expressed in cells. We generated a form of srIκBα in which its N terminus is fused to the protein transduction domain of HIV TAT (TAT-srIκBα). Purified TAT-srIκBα protein rapidly and efficiently entered HeLa or Jurkat T cells. TAT-srIκBα, when exogenously added to HeLa cells, inhibited in a dose-dependent manner TNF-α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Our results showed that L-arginine treatment has an inhibitory effect on the total NF-B level in mdx diaphragm and concomitant inhibition of IB-␣ degradation ( Figure 3). In line with previous reports, 30 we suggest that the decreased level of inflammatory cytokines (TNF-␣, IL-1␤, and IL-6) after L-arginine treatment could directly affect the expression level and the activity of NF-B in dystrophic muscle myofibers. Moreover, one of the mechanisms by which NF-B signaling appears to contribute to dystrophy is by promoting chronic inflammation.…”
Section: L-arginine Down-regulates Nf-b Activity In MDX Musclesupporting
confidence: 93%
“…Our results showed that L-arginine treatment has an inhibitory effect on the total NF-B level in mdx diaphragm and concomitant inhibition of IB-␣ degradation ( Figure 3). In line with previous reports, 30 we suggest that the decreased level of inflammatory cytokines (TNF-␣, IL-1␤, and IL-6) after L-arginine treatment could directly affect the expression level and the activity of NF-B in dystrophic muscle myofibers. Moreover, one of the mechanisms by which NF-B signaling appears to contribute to dystrophy is by promoting chronic inflammation.…”
Section: L-arginine Down-regulates Nf-b Activity In MDX Musclesupporting
confidence: 93%
“…In the case of Tat, it has been demonstrated that the intraperitoneal injection of a 120-kDa ␤-galactosidase/Tat fusion protein results in the transcellular transduction into virtually all tissues in mice, including the passage of the blood-brain barrier (12). Based on these observations, the translocating activity of the Tat basic domain is now being extensively utilized for several therapeutic applications, including protection from apoptosis in the brain (13,14) and in the heart (15), extension of the cytotoxic activity of herpes simplex virus-1 thymidine kinase for cancer gene therapy (16), improvement of the IB␣ activity (17), enhancement of antigen presentation by dendritic cells (18,19), quenching of the tumor phenotype (20), and enhancement of viral-mediated gene delivery (21), to name but a few of the current applications. In addition, the Tat transduction domain has also been shown to mediate cell internalization of large molecules or particles, including magnetic nanoparticles (22), phage vectors (23), liposomes (24), and plasmid DNA (25).…”
mentioning
confidence: 99%
“…These include Grb2-binding peptide (16), mitogen-activated protein kinase (17), STAT3 (18), NEMO-IKK-interacting peptide (19), and peptides carrying nuclear localization sequences (20 -23). Besides peptides, PTD have also been used to deliver larger full-length polypeptides, including IB␣ (24), cyclin-dependent kinase inhibitory protein p27 (25), antiapoptotic protein Bcl-x L (26), and proapoptotic proteins (27).…”
mentioning
confidence: 99%